Impact of ETF Listing on the Returns Generated by Underlying Stocks: Indian Evidence. (August 2021) - Kaur, Prabhdeep; Singh, Jaspal
The advent of exchange traded funds (ETFs) has rendered index trading much affordable compared to their futures counterparts. The present study attempts to examine the impact of ETF listing on the price of the constituent securities of the index that it aims to track. The sample comprises of all the equity ETFs listed in India from 1 January 2002 to 31 March 2019. Event study analysis has been used to examine whether listing of ETFs bore any price impact on the constituent stocks of ETFs. To account for robustness, both parametric and non-parametric tests have been employed. The estimates obtained from event study analysis revealed that the constituent stocks generated insignificant returns for the period extending from January 2002 to March 2009 and April 2009 to March 2013 but positive and significant cumulative average abnormal returns (CAARs) post ETF listing for the period ranging from April 2013 to March 2019, thus providing evidence in support of positive price impact. The permission granted to pension funds, insurers and Employees' Provident Fund Organisation (EPFO) to invest their funds in ETFs as well as reduction in Securities Transaction Tax (STT) account for the observed price differential. An analysis of the factors accounting for the variation in valuation effects ascertained that the stocks that were traded thinly prior to ETF listing and those forming part of ETFs with larger asset base experienced positive price impact following ETF listing. JEL Codes: G11, G14